APIP dalam Pelaksanaan Maturitas SPIP: Government Internal Supervisory Apparatus in Implementing the Maturity of the Government Internal Control System - Djamil, Nasrullah (JAAMTER : Jurnal Audit Akuntansi Manajemen Terintegrasi, 2023)
One of the problems that still occur in Indonesia today is the weakness of the Government Internal Control System (SPIP). This is indicated by the many findings of BPK's examination of weaknesses in the government's internal control system. In this case, there is a role for government internal auditors that are highly expected to create an effective and sustainable control system. This study aims to determine the effect of the role of APIP in implementing the Maturity of the SPIP at the Inspectorate Kab. South Solok. This research is a quantitative. The population and sample in this research were all government internal supervisory apparatus at the Inspectorate Kab. South Solok. Data collection technique used is through a questionnaire. The analysis technique used in this research is descriptive statistical analysis. The instrument were tested using validity test, reliability test, and normality test. Data analysis technique used is multiple linear regression analysis. The results showed that the role of leadership, internal supervisors, consultants, and catalysts had a positive effect on the implementation of the maturity of SPIP. While the role of quality assurance has a negative effect on the implementation of the maturity of SPIP.